SALTO Projects Awards Finalist - Michael-Grigoriou, Despina (My University, 2026)
The VRTEACHER project, in which I was participating as a consortium member, made it for the Salto Awards Finals 2023, the annual contest promoting great projects all over the Europe. Only 15 projects made if for the finals out of more than 200 participations. https://participationpool.eu/2023/09/20/discover-the-finalists-of-the-salto-awards-2023/
Keywords: Sciences